Local Content in the Oil and Gas Sector - Tordo, Silvana; Warner, Michael; Manzano, Osmel E.; Anouti, Yahya (Washington, DC: World Bank, 2013)
A number of countries have recently discovered and are developing oil and gas reserves. Policy makers in such countries are anxious to obtain the greatest benefits for their economies from the extraction of these exhaustible resources by designing appropriate policies to achieve desired goals. One important theme of such policies is the so-called local content created by the sector- the extent to which the output of the extractive industry sector generates further benefits to the economy beyond the direct contribution of its value-added, through its links to other sectors. Local Content Policies (LCPs) were first introduced in the North sea in the early 1970s and ranged from restrictions on imports to direct state intervention in the oil sector. While LCPs have the potential to stimulate broad-based economic development, which is necessary to alleviate poverty and achieve the United Nation's Millennium Development Goals (MDGs), their application in petroleum-rich countries has achieved mixed results. This paper serves to introduce the topic by describing policies and practices meant to foster the development of economic links from the petroleum sector, as adopted by a number of petroleum-producing countries both in and outside the Organization for Economic Co-operation and Development (OECD). The paper is organized as follows: chapter one defines local content and briefly illustrates the links between the petroleum sector and other economic sectors (where policies may be able to increase the economic benefits of the petroleum sector). An attempt is made to measure local content levels in a wide sample of petroleum-producing countries including net importers and net exporters, and countries at different stages of economic development to put LCPs in context and to consider if the structure of an economy is a key driver of local content levels. Chapter two discusses the arguments that have been used in favor and against the use of productive development policies in general and LCPs in particular. Chapter three provides an outline of the tools and types of LCPs that have been used by petroleum producing countries, and present their strengths and weaknesses. Chapter four focuses on issues related to the measurement and monitoring of LCPs, and discusses the limitations of alternative metrics. Chapter five provides a description of LCP objectives, implementation tools, and reporting metrics used in a selected sample of oil-producing countries including Angola, Brazil, Kazakhstan, Indonesia, Malaysia, and Trinidad and Tobago and draw initial lessons that may be relevant to other countries.